ANALISIS PENGUJIAN PENAMBAHAN BAJA RINGAN UNTUK MENINGKATKAN KUAT LENTUR BETON - Rosyad, Farlin; Winanda, Ario Tri (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
This research aims to determine the results of the effect of adding pieces of tire rubber on the flexural strength of concrete. This research was conducted at the Civil Engineering Laboratory, Campus C, Bina Darma University. The object used in this research is the effect of adding light steel pieces on the flexural strength of concrete with percentages of 5%, 10% and 15%. The results of research and analysis regarding the influence of adding light steel pieces on the flexural strength of concrete in the form of small pieces measuring 2 cm long and2 mm wide have a very positive impact on the flexural strength value, this is in line with the increase in the flexural strength value for each percentage of the object. tests such as normal concrete have an average flexural strength value of 3.25 Mpa, the 5% percentage has an average flexural strength value of 6.41 Mpa,the 10% percentage has an average flexural strength value of 7.40 Mpa, and15%has an average flexural strength value of 5.59 Mpa, meaning there is an increase in the normal concrete flexural strength value of 3.25 Mpa. So these pieces of tire rubber have a positive effect and are suitable as an alternative addition to modified concrete mixes, and are suitable for use in structural concrete beams in residential buildings, house foundations and bridges.